Penggunaan Google Classroom Pada Mata Kuliah PAI - Hilyah Ashoumi; Mochammad Syafiuddin Shobirin (Universitas KH. A. Wahab Hasbullah, 2019)
This research aims to increase student participation in the teaching and learning process, because Google classroom has a broad and unlimited discussion space, where lecturers can create virtual classes in interaction with students. Google classroom has features that can be used in the teaching and learning process including the main page that can display students' assignments, classroom management in accordance with the wishes of educators, storage in Google Drive, can be accessed via smartphone, can accommodate all types of files, and can add a profile picture. In addition there are other features that can be used by lecturers in developing material, namely Reusepost, Createquestion, Createassignment, and Createannouncement. The research method used in this study is a qualitative research method in the form of field research. The results of the use of Google Classroom media were applied to the design of PAI course lectures consisting of two aspects namely lecture material and lecture methods. Lecture material that is presented in an organized and structured, while the lecture methods developed are divided into two, namely in groups and individually. The results of this study are an increase in 80% student participation as measured using a Likert scale. Keywords: Google Classroom, Islamic Education.